Fundamentals of Islamic aqidah - Abdul Rahim, Adibah (2017)
Living in the age of globalization, Muslims are facing so many temptations in life to direct their intention and turn their interest away from the right course of religion. The study of Islamic aqidah is very important to make Muslims aware of the correct knowledge and understanding of Islam, and about being Muslims or what it really means to be Muslims. Its content is worth learning because it is meaningful and relevant to our everyday lives. One of the major concerns of Islamic aqidah is its belief systems and its views particularly on the concept of tawhid, life after death, the concept of fitrah, man and society. These topics will not be approached from theological or philosophical perspectives rather practical in nature. The purpose is to create awareness among Muslims of what are the implications of those beliefs on their lives. There is no doubt that the study of Islamic aqidah plays an important role in developing the development of Muslims’ characters. Therefore, this study is aimed at acquainting Muslims with the proper understanding on the concept of Islamic aqidah and its main foundations, and at the same time celebrating the possibility of analytical method in the study of aqidah. It is hoped that Muslims may be able to translate and apply the various concepts and principles of Islamic aqidah in their individual and social context